The clique : a novel - Harrison, Lisi (Little, Brown, 2004)
Wealthy Massie is determined to exclude middle class Claire, the daughter of her father's old friend, from her seventh-grade clique at a very exclusive private school in Westchester, New York, but after Massie steals her only friend, Claire strikes back.